Depoimento especial: uma necessária conversa entre o direito e a psicologia - Xavier, Anna Carolina de Paula (2018)
In the current context of the Judiciary, professionals from different areas have been debating the Special Testimony, an inquiry methodology used when working with children and adolescents victims of sexual violence, resulting in divergent arguments on the subject. Our study aims to present these dissonant positions among legal professionals regarding the Special Testimony, seeking to make possible a current and comprehensive view on this procedural act. In this scenario, the judicial system and the psychology professionals need to strengthen their abilities in order to work together in a respectful, multidisciplinary and equitable exchange of knowledge. It is fundamental to apply this new methodology, since it is possible and necessary. However, this must be done in a defined format of dialogue between the existing knowledge, so that it is efficient and effective in protecting the child and adolescent victims of sexual abuse. We also intended to describe, characterize, analyze and evaluate how the Judges of the Counties of the Southern region of Brazil have applied the Special Testimony in their respective regions. Our objective was to broaden the technical and methodological debate between Psychology and Law in the process of greater understanding of this procedure.